The benefits of simply observing mindful attention modulates the link between motivation and behavior. [article]. - Papies, Esther; Pronk, Tila M.; Keesman, Mike.
Mindful attention, a central component of mindfulness meditation, can be conceived as becoming aware of one?s thoughts and experiences and being able to observe them as transient mental events. Here we present a series of studies demonstrating the effects of applying this metacognitive perceptive to one?s spontaneous reward responses when encountering attractive stimuli. Taking a grounded cognition perspective, we argue that reward stimulations in response to attractive stimuli contribute to appetitive behavior and that motivational states and traits enhanced these stimulations. Directing mindful attention at these thoughts and seeing them as mere mental events should break this link, such that motivational states and traits no longer affect reward stimulation and appetitive behavior to test this account, we trained participants to observe thoughts in reaction to appetitive stimuli as mental events, using a brief procedure designed for nonmediators. Across 3 experiments, we found that adopting the mindful attention perspectives reduced the effects of motivational states and traits on appetitive behavior in 2 domains, in both the laboratory and the field. Specifically, after applying mindful attention, participants? sexual motivation no longer made opposite-sex other seemed more attractive and thus desirable as partners. Similarly, participants? levels of hunger no longer boosted the attractiveness of unhealthy foods, resulting in healthier eating choices. We discuss these results in the context of mechanisms and applications of mindful attention and explore how mindfulness and mindful attention can be conceptualized in psychological research more generally. - - (from the authors)
Keywords: Mindfulness-Periodicals.; Decentering-Periodicals.; Ground cognition-Periodicals.; Eating behavior-Periodicals.